Fire Alarm Bluetooth Truck - Kunwar, Akshay; Singh, Jai; Kushwaha, Ayank (Indian Journal of Computer Science, 2020)
Fire accidents are very common in our surroundings and it is not practically possible to assign a fireman everywhere to determine whether any fire casualty is happening in the area. Fire Alarm Bluetooth Truck is an Arduino device which can easily solve this problem. These Arduino trucks detect fire in a particular range and because of their mobility, they immediately reach the place of the mishap. The trucks have a water tanker through which they take water and sprinkle on the fire to extinguish it. This machine gets commands from the mobile phone with the help of Bluetooth. These Arduino trucks are very easy to use and as they function with the help of Bluetooth, they can easily be used in day to day life.